Performance of Bamboo Handicraft MSMEs as a Source of Supplementary Income in Wonokarto Village, East Lampung (International Journal of Applied Research and Innovation, 2026)
Bamboo weaving micro, small, and medium enterprises (MSMEs) play an important role in supporting rural household income in Wonokarto Village, East Lampung, yet their performance is constrained by irregular bamboo raw material availability and operational limitations. This study aims to analyze bamboo availability, identify the factors influencing MSME performance, and evaluate the income generated by bamboo weaving enterprises. An empirical mixed-methods approach was employed using census sampling involving 42 bamboo weaving artisans. Primary data were collected through questionnaires, interviews, field observations, and documentation, while secondary data were obtained from official statistics and relevant literature. Bamboo availability was analyzed descriptively, MSME performance determinants were examined using ordinal logistic regression, and income was estimated through revenue-cost analysis. The results indicate that bamboo availability is generally adequate but remains constrained by inconsistent supply continuity. Time efficiency and production output significantly influence MSME performance, with odds ratios of 18.37 and 21.01, respectively, whereas cost efficiency and product diversification show no significant effects. The regression model explains 49.3% of the variation in MSME performance. Average monthly production reached 49 units, generating a net income of IDR 1,161,798.13, with kurungan ayam balian accounting for 41% of total sales